Varicella-zoster Virus - Abendroth, Allison.; Abendroth, Allison.; Arvin, Ann M.; Arvin, Ann M.; Moffat, Jennifer F.; Moffat, Jennifer F. (Current Topics in Microbiology and Immunology, 2010)
Varicella-zoster virus is a common human pathogen that causes varicella (chickenpox), establishes latency in sensory nerve ganglia and can reactivate many years later as herpes zoster. Although the VZV genome is the smallest of the human herpesviruses, VZV genes encode at least 70 proteins. Molecular epidemiologic approaches based on genomic sequencing have documented the global distribution of VZV in distinct clades that reflect patterns of human migration. Contemporary molecular methods are making it possible to dissect how VZV gene products support the viral life cycle, including those that are necessary for viral replication, virion assembly and egress as well as those that permit take over of the host cell by modulating cell cycle regulation, survival and intrinsic antiviral responses. Progress is also being made in understanding the events in VZV pathogenesis and the viral tropisms for keratinocytes, T cells, dendritic cells and neurons during primary infection, latency and reactivation and the innate and adaptive host responses that modulate these events. New insights about molecular virology and pathogenesis have emerged from comparative studies of VZV and simian varicella virus. VZV is the only human herpesvirus for which vaccines to prevent both primary and recurrent infection are approved and VZV vaccines have had significant public health benefits. These achievements and new directions that are unfolding are described in this review of VZV basic and clinical research.